Optimasi formula serbuk kopi hijau dengan mixture design - Andi Eko Wiyono; Yuli Wibowo; Vinka Oktavia Pramesti (AGROINTEK, 2026)
Green coffee is coffee that does not go through a roasting process and has the main bioactive component as an antioxidant. Green coffee's liquid extract is generally used as a raw material or additional ingredient in food and non-food products. However, extracts in liquid form are easily damaged. Another effort that can be made to protect the antioxidant content of green coffee extract is to process it into green coffee powder using a foam mat drying technique. This research aims to obtain the optimum formula and determine the physical, chemical, and organoleptic characteristics of green coffee powder with variations of maltodextrin and tween 80 using the simplex lattice design method. The research design uses laboratory experimental methods with quantitative data analysis. Optimization parameters include water content tests, total dissolved solids, pH, dissolution rate, yield, and color. Supporting parameters include antioxidant activity tests, organoleptic, and ⁰hue value. The research results showed that the optimum formula for green coffee powder at a maltodextrin concentration of 0.97⁰ and tween 80 0.03% had a percentage resistance value to DPPH between 44.25-75.68% with an IC50 value of 65.15 ppm in the strong category; organoleptic parameters bright color, strong aroma, and neutral taste; The ⁰Hue value obtained is 90, including the color yellow (Y).